2004
DOI: 10.1158/1078-0432.ccr-03-0122
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Conditionally Replicative Adenovirus Vector Targeting Telomerase-Positive Tumor Cells

Abstract: Purpose: To develop a novel conditionally replicative adenovirus vector that targets telomerase-positive cancer cells.Experimental Design: A telomerase gene-derived promoter was used to control the expression of the E1a gene so that the E1a gene is only expressed in telomerase-positive tumor cells. In addition, a reporter gene was also engineered into the vector so that its infection and replication can be monitored easily. Conclusions: The telomerase-targeted adenovirus vector has significant potential as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Selective cytolysis of telomerase-positive cells was observed and administration of the viral mutant to tumor xenografts resulted in significant inhibition of tumor growth. 94,95 Growth factor receptors are also often upregulated in tumor cells. One study showed that an adenovirus mutant, containing the E1 gene under control of a vascular endothelial growth factor receptor (flt-1) promoter, was specifically targeted to teratocarcinoma cell lines.…”
Section: Viral Dependency On Tissue/tumor-specific Promotersmentioning
confidence: 99%
“…Selective cytolysis of telomerase-positive cells was observed and administration of the viral mutant to tumor xenografts resulted in significant inhibition of tumor growth. 94,95 Growth factor receptors are also often upregulated in tumor cells. One study showed that an adenovirus mutant, containing the E1 gene under control of a vascular endothelial growth factor receptor (flt-1) promoter, was specifically targeted to teratocarcinoma cell lines.…”
Section: Viral Dependency On Tissue/tumor-specific Promotersmentioning
confidence: 99%
“…Both plasmids were transfected into Ad293 cells by the use of Lipofectamine 2000 (Invitrogen). Ad-enhanced green fluorescent protein (EGFP) (an E1 deleted replication-deficient adenovirus with EGFP expression cassette), Ad-null (an E1 deleted replicationdeficient adenovirus without any exogenous gene), Ad-TERT-E1A/E1B (a replication-competent adenovirus with telomerase reverse transcriptase promoter-driven E1A/E1B expression cassette) 25 and dl309 (an adenoviral mutant with intact E1) were made or maintained earlier in our laboratory.…”
Section: Construction Package and Preparation Of Adenovirusmentioning
confidence: 99%
“…Normal adult tissues, with few exceptions, do not express this protein (14). Telomerase is also targeted because of the critical role it plays in tumor development and survival (13,(15)(16)(17)(18)(19)(20). The therapeutic strategies under investigation include functional inhibition by genetic and pharmacologic approaches (15,16,18,19) as well as immunotherapy (20).…”
Section: Introductionmentioning
confidence: 99%